KEDUDUKAN ANAK ANGKAT DALAM HUKUM WARIS ISLAM DAN HINDU - Zakiyatul Ulya (State Islamic University (UIN) of Sunan Ampel, 2017)
Both of Islam and Hindu have regulated in detail the issues of inheritance. If the two are compared, it can be seen that there is a difference in positioning adopted child, where in Hindu law is used as the cause of inheritance whereas in Islamic law it is not. Thus, it can be seen that the adopted child does not belong to the heirs in Islamic law, so the inheritance rights remain to his biological family, not his adopted family. However, they can get a share of the property of their adopted parents by the way of a testament not more than 1/3 of a part, even in this case, article 209 paragraph 2 of KHI states that against a adopted child who does not receive a will is given a maximum of 1/3 of the inheritance of his adopted parents. Unlike the Islamic law, Hindu law classifies adopted sons including in heirs whose inheritance rights are transferred to their adopted families and are equal to those of legitimated children who inherit in the first place with the possibility to obtain all parts if no children are equal.